Pre-energize Analysis on 3 Phase Transformer by Considering Each Phase Flux - Hadwim Septiawan; I Made Yulistya Negara; Feby Agung Pamuji (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
Inrush current is a transient phenomenon that occurs when a transformer is first energized to a voltage source at no-load conditions. It causes a very high inrush current. Inrush currents can adversely affect the electric power system and can cause improper work of a relay protection errors. The purpose of this study is to determine the amount of inrush current and minimize the amount of inrush current by using the pre-fluxing method. In this study, a test was carried out using a 3-kVA core type 3 phase transformer. This test is done by giving DC flux before the transformer is connected to the voltage source, then the three transformer phases are energized simultaneously at a certain voltage angle so that the inrush current may could be minimized. The test results show that the transformer that is given a DC flux always has a relatively small inrush current. In this test the inrush current is reduced to a minimum value at an ignition angle of 90 degrees with an inrush current value of 0.74 A in phase R, 3.41 A in phase S, and 3.80 A in phase T.Keywords: flux, inrush current, transformer, transient.